ANALISIS PENGARUH KREDIBILITAS INFLUENCER DAN DISCLOSURE OF SPONSORSHIP TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MELALUI BRAND ATTITUDE SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Generasi Z di Instagram) - Ariq Naufa Prasetio; Farida Indriani (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study examines the impact of influencer credibility and sponsorship disclosure in influencer marketing activities to establish consumer attitudes (brand attitudes) and their impact on purchasing decisions. The population used in this study are consumers of the z generation who are active users of Instagram social media. The number of respondents in this study amounted to 100, with the data collection method done through a questionnaire. The analysis in this study was carried out using the SPSS analysis tool. The results of this study indicate that including influencer credibility and sponsorship disclosure in influencer marketing activities carried out on Instagram can positively affect brand attitude. After that, the brand attitude that is built also has a positive effect on consumer purchasing decisions.